INDIVIDUAL COMPETENCY CAUSAL FACTORS AFFECTING PERFORMANCE OF ACADEMIC PERSONNEL IN HIGHER EDUCATION INSTITUTION - Chanyaphak Lalaeng; Mallika Subongkod (Zenodo (CERN European Organization for Nuclear Research), 2021)
Abstract: The objective of this research was to test an individual competency causal model affecting performance of personnel in higher education institutions. The study was conducted among education institutions in the upper southern of Thailand. The instrument used in the study was questionnaire. Data analysis was conducted using descriptive statistics, Pearson’s correlation coefficient, confirmatory factor analysis, and causal factor analysis. The findings from the study found that 1) the individual competency causal model had an effect on performance of personnel in higher education institutions. It was consistent with the empirical data, considered from χ² = 994.860, df = 249, p = 0.000, χ ²/ df = 3.99, CFI = 0.94, TLI = 0.93, RMSEA = 0.06, SRMR = 0.04. Individual competency causal factors had an effect on performance of personnel with statistical significance. All predictor variables in the model could describe variance of performance, core competency, and job competency by 70.0%, 83.0% and 88.0% respectively.
Keywords: Organizational Leadership and Management Strategies